Segurança/insegurança alimentar em famílias urbanas e rurais no estado do Amazonas: I. validação de metodologia e de instrumento de coleta de informação - Yuyama, Lucia Kiyoko Ozaki; Aguiar, Jaime Paiva Lopes; Pantoja, Lilian; Maeda, Roberto Nobuyuki; Melo, Tatiana; Alencar, Fernando Hélio; Nascimento, Angela M. Matos; Negreiros, Neide M. Almeida; Corrêa, Ana Maria Segall; Pérez-escamilla, Rafael (Acta Amazonica, 2007)
The present study validates the methodology and the information collecting instrument for analysis of nutritional security/insecurity on the urban and rural family level, proposed by the USDA (United States Department of Agriculture). An intentional sample of domiciles was selected to represent different social strata, 194 families were enrolled in urban Manaus, of which 174 had children, in the following neighborhoods: Jesus me Deu, Nova Israel, Cidade Nova, Coroado and Conj. Petro. In the rural area between the municipalities of Iranduba and Manacapuru, 209 riparian families were interviewed, and of these 131 had children. The final validation of the questionnaire (global internal consistency) was made by comparing, the levels of nutritional security/insecurity, with the defined social strata and food consumption indicators. The results demonstrated that the groups of highest nutritional insecurity were the very poor. The instrument presented high validation and internal consistency.
Nutritional security/insecurity in urban and rural families of Amazonas state: validation of methodology and of information collecting instrument
Keywords: Nutritional Security; Nutritional Security; Quantitative Validation; Segurança Alimentar; Insegurança Alimentar; Validação Quantitativa